Pendidikan Kesehatan Tentang Bahaya Merokok Kelas XII Di SMK 23 Maret Kotamobagu - Rusdiyana Magulili; Iyan Jakaria; Nadea Lasasbuda; Sinta Yunita; Siti Faradila Amirudin; Ria. SC Angelita Lawere; Mutiara Dyina Sari Laya; Yulianira Yulianira; M Puha (Jurnal Insan Pengabdian Indonesia, 2023)
Based on the results of surveys, interviews and observations, it was found that youth problems at SMK 23 Maret Kotamobagu, especially in class XII, namely smoking. health education about the dangers of smoking at SMK 23 Maret Kotamobagu is also still lacking, especially in class XII students due to the lack of attention from teachers to students, therefore we, Manado Muhammadiyah University students, raise this title. The aim is to increase students' knowledge and awareness about.